Globalization and its discontents - Stiglitz, Joseph E. (New York : W. W. Norton, 2002)
Former World Bank chief economist Joseph E. Stiglitz expresses his disillusionment with international institutions and Washington policy makers regarding the global economy, discussing the plight of poor nations, the East Asia crisis, and the former Soviet economies.
Includes bibliographical references and index.
Booklist.
Library Journal.
Pub Weekly.
Adult
Keywords: International Monetary Fund -- Developing countries; International Monetary Fund; Foreign trade regulation; Globalization -- Economic aspects -- Developing countries; International economic integration; International finance; Commercial law; Commercial policy -- United States; Finance; Globalization -- Economic aspects; International economic relations; International economic relations; United States -- Commercial policy; Developing countries